2012
DOI: 10.1186/1475-2875-11-91
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic anaemia in an HIV-infected patient with severe falciparum malaria after treatment with oral artemether-lumefantrine

Abstract: Intravenous (i.v.) artesunate is now the recommended first-line treatment of severe falciparum malaria in adults and children by WHO guidelines. Nevertheless, several cases of haemolytic anaemia due to i.v. artesunate treatment have been reported. This paper describes the case of an HIV-infected patient with severe falciparum malaria who was diagnosed with haemolytic anaemia after treatment with oral artemether-lumefantrine.The patient presented with fever, headache, and arthromyalgia after returning from Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 12 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][21][22][23][24] One study was excluded from further analysis, 12 since the reported patients were part of a second publication, which was used for the purpose of this systematic review. 13 In addition to the above-mentioned scientific papers, reports by the Centers for Disease Control and Prevention (CDC, Atlanta, USA) 25 and by the Medicines for Malaria Venture (Geneva, Switzerland) were identified and included in this analysis 26 ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[12][13][14][15][16][17][18][19][21][22][23][24] One study was excluded from further analysis, 12 since the reported patients were part of a second publication, which was used for the purpose of this systematic review. 13 In addition to the above-mentioned scientific papers, reports by the Centers for Disease Control and Prevention (CDC, Atlanta, USA) 25 and by the Medicines for Malaria Venture (Geneva, Switzerland) were identified and included in this analysis 26 ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19]21,23,24,26 Thirty-three cases have been published in research papers and four cases are referred to in a meeting report (one from China, one from the USA, and two from Canada). 26 In addition, surveillance data from France were discussed in that report but have not yet been published and were therefore not available for the purpose of this review.…”
Section: Description Of Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 There are a few cases in the literature of hemolytic anemia during or after treatment with intravenous artesunate alone or in combination with mefloquine, and one report after oral treatment with AL in a (G6PD normal) patient with HIV and severe falciparum malaria. 44 However, these are rare adverse events. It appears that clinically, in the majority of patients administered artemisinins, the presence of malaria and dehydration rather than the drug exert the most important effects on hematologic parameters.…”
Section: Hemolysis and Almentioning
confidence: 99%